The Antioxidant Properties of Black Garlic Aqueous Extract in Vero Cell Line - Marie, Amna Mohamed Abdulhafith; Wijayanti, Nastiti (Proceeding International Conference on Science and Engineering, 2020)
Oxidative stress has been defined as harmful because oxygen free radical attack biological molecules such as lipids, proteins and DNA. Antioxidants are substances that can prevent or slow damage to cells caused by free radicals, unstable molecules that the body produces as a reaction to environmental and other pressures. Black garlic (BG) is one of the natural resources that has been reported to have antioxidant properties. The aims of this research was to study the potential and effect of BG as antioxidant in LPS induced Vero cells. The methods of this research were used the extraction of BG by maceration method using aqueous solvents, antioxidant activity tested using DPPH assay, cytotoxicity test with WST-1 assay on 96-well plate, and NO level measurement using Griess reagent, after cells induced with LPS. The result showed that in DPPH assays BG showed ability for scavenging free radical activities. The BG aqueous extract did not show cytotoxicity on Vero cells until the concentration of 750µg/ml and NO levels decreased in cells treated with a concentration of 50 µg/mL after LPS induction. This study concluded that the administration of aqueous extract of Black Garlic has the potential as an antioxidant.